Pseudoxanthoma Elasticum is a Metabolic Disease - Jiang, Qiujie (2008)
Pseudoxanthoma elasticum (PXE) is a pleiotropic multisystem disorder affecting skin, eyes, and the cardiovascular system with progressive pathological mineralization. It is caused by mutations in the ABCC6 gene expressed primarily in the liver and kidneys, and at very low levels, if at all, in tissues affected by PXE. A question has arisen regarding the pathomechanism of PXE, particularly the “metabolic” versus the “PXE cell” hypotheses. We examined a murine PXE model (Abcc6(−/−)) by transplanting muzzle skin from knock-out (KO) and wild-type (WT) mice onto the back of WT and KO mice using mineralization of the connective tissue capsule surrounding the vibrissae as an early phenotypic biomarker. Grafting of WT mouse muzzle skin onto the back of KO mice resulted in mineralization of vibrissae, while grafting KO mouse muzzle skin onto the WT mice did not. Thus, these findings implicate circulatory factors as a critical component of the mineralization process. This mouse grafting model supports the notion that PXE is a systemic metabolic disorder with secondary mineralization of connective tissues and that the mineralization process can be countered or even reversed by changes in the homeostatic milieu.